Susan Sontag — zapomniana matka? - Ziewiec, Kludia (Poznańskie Studia Polonistyczne. Seria Literacka, 2013)
The article discusses new and republished translations of Susan Sontag’s work, recently launched by the Karakter publishing house: Regarding the Pan of Others, On Photography, and Against Interpretation and Other Essays. The article focuses on the elements of Sontag’s thought that make her a forgotten mother of feminist and gender theoreticians, as well as such influential critics as Michel Foucault and Roland Barthes. The article points out to continuations of Sontag’s thought in contemporary theoretical and social projects, and to the pertinence of her critical observations on theories based on metaphysics of presence: psychoanalysis, Marxism, or hermeneutics. The article also touches upon history of war photography and related war journalism, and upon the ambivalent quality of imaging of the misery of war. It also present historical and cultural circumstances of the development of Sontag’s thought in the intellectual milieu of New York in the 1960s. The discussion recapitulates the main statements of Sontag’s essays, relating them to a wider theoretical context, which is aimed at a reappraisal of the forgotten intelectual in the history of literature.